Implementasi pendidikan akhlak dan moral pada siswi perspektif kitab al-akhlaq lil banat - Syarifah, Hasnia Imroatis (Maliki Interdisciplinary Journal, 2024)
The moral decline of students is one of the impacts of globalisation. The facts circulating show that there is a drastic decline in the morals of youth, especially among women. One of the rampant cases is the decline in women’s morals that are not in accordance with Islamic values, even around fifty thousand underage girls have registered marriage with the religious affairs office on the grounds of being pregnant outside of marriage. Based on this reality, this study aims to implement morals and morals that are in accordance with Islamic religious values in female students through akhlaqul lil banat. The method used is putaka study or library research on books, journals, and literature related to moral and moral education and the book of Al-Akhlaq Lil Banat. This research shows that the students of the Roudlotut Tholibin madrasa diniah are able to have morals and morals in accordance with the book of Al-Akhlaqul Lil Banat. Second, learning in the book of akhlaqul lil banat can provide a solution to the moral decline of the nation’s girls. Third, to arrive at the above solution, the effective method used on female students is learning the book of akhlaqul lil banat at Madrasah Diniyah Roudlotut Tholibin and its practice in everyday life.